Integrative Framework of Instructional Strategies and Learning Design: A Systematic Conceptual Literature Review - Latif. R, Abd.; Rizki, Miftahul; Hazmi, Deni; Nasution, Wahyudin Nur; Haidir, Haidir (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
Twenty-first-century learning requires adaptive, integrated, and contextual learning strategies and designs to develop learners' competencies and character. This literature review aims to create a comprehensive conceptual understanding of instructional strategies, learning design frameworks, instructional design elements, and teaching strategies in Islamic education. This study employs a qualitative approach using the Systematic Conceptual Literature Review (SCLR) method. A total of 40 scientific articles published between 2014 and 2024 were systematically analyzed, including Scopus-indexed journals, Google Scholar, academic books, and educational policy documents. The search was conducted through Scopus, Google Scholar, DOAJ, and ProQuest in Indonesian and English, then analyzed using thematic analysis and conceptual synthesis to identify functional and structural relationships among the components of instructional strategies. The findings indicate that effective learning is determined by integrating instructional strategy components, including clear objectives, logical sequencing of materials, meaningful activities, and continuous evaluation. The learning design framework is a conceptual map connecting objectives, learning experiences, and technology utilization, with a flexible and modular design practical for e-learning, mobile learning, and MOOCs. In Islamic education, contextual strategies integrating traditional methods such as Qur’anic stories and nasheed with technology-based collaborative approaches enhance student engagement and value internalization